2021
DOI: 10.1177/02537176211030993
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Responsibility in Geropsychiatry: Competence, Culpability, and Care

Abstract: Elderly persons can get involved in the criminal justice system as victims or as perpetrators. The interaction of elderly persons with mental illness at various cross-sections of the judicial process needs thoughtful consideration. Through this review, the authors approach this less studied aspect of forensic psychiatry. Concerning the evaluation of a prisoner, three scenarios need focused consideration: evaluation for fitness to stand trial before a competent court, evaluations for an insanity defense, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Challenges included a lack of: procedure regarding further assessment for people of concern Tilsed, 2019;Treacy et al, 2019;Turner, 2018); limited staff knowledge (Forsyth, Heathcote and Senior et al 2020); staff confidence in diagnosing dementia Treacy et al, 2019), including prison healthcare staff delaying diagnosis Treacy et al, 2019); lack of training and, particularly in local prisons (Forsyth, Heathcote and Senior et al 2020); regular health-checks for long-stay prisoners Brown, 2016); time and resources (Turner, 2018;Correctional Investigator Canada, 2019;Inspector of Custodial Services, 2015;Goulding, 2013); the high turnover of prisoners (Forsyth, Heathcote and Senior et al 2020) and; prison-specific screening or assessment tool(s) Patterson et al, 2016;Turner, 2018;Correctional Investigator Canada, 2019;Feczko, 2014; National Institute for Health and Care Excellence, 2017). Problematically, prisoners tend to underreport any cognitive or physical symptoms either for fear of repercussions (Pandey et al, 2021) or because of poor insight into their cognitive impairment and deteriorating health (du Toit et al, 2019) and it was reported that some people did not attend assessments for fear of bullying from other prisoners (Murray, 2004). Further to this, ensuring that consent is given freely by an incarcerated individual (who may also have dementia) is challenging.…”
Section: Table 3 Challenges To Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Challenges included a lack of: procedure regarding further assessment for people of concern Tilsed, 2019;Treacy et al, 2019;Turner, 2018); limited staff knowledge (Forsyth, Heathcote and Senior et al 2020); staff confidence in diagnosing dementia Treacy et al, 2019), including prison healthcare staff delaying diagnosis Treacy et al, 2019); lack of training and, particularly in local prisons (Forsyth, Heathcote and Senior et al 2020); regular health-checks for long-stay prisoners Brown, 2016); time and resources (Turner, 2018;Correctional Investigator Canada, 2019;Inspector of Custodial Services, 2015;Goulding, 2013); the high turnover of prisoners (Forsyth, Heathcote and Senior et al 2020) and; prison-specific screening or assessment tool(s) Patterson et al, 2016;Turner, 2018;Correctional Investigator Canada, 2019;Feczko, 2014; National Institute for Health and Care Excellence, 2017). Problematically, prisoners tend to underreport any cognitive or physical symptoms either for fear of repercussions (Pandey et al, 2021) or because of poor insight into their cognitive impairment and deteriorating health (du Toit et al, 2019) and it was reported that some people did not attend assessments for fear of bullying from other prisoners (Murray, 2004). Further to this, ensuring that consent is given freely by an incarcerated individual (who may also have dementia) is challenging.…”
Section: Table 3 Challenges To Assessmentmentioning
confidence: 99%
“…Regarding family, many hospices were described as allowing more visits Goulding, 2013 Fazel et al, 2002); staff resistance (Turner, 2018); lack of understanding of the prison context Williams, 2014); high levels of staff burnout ; people not accessing healthcare for fear of bullying (Cipriani et al 2017); not being able to physically access healthcare centres (Treacy et al, 2019; Her Majesty's Inspectorate of Prisons, 2017b; Welsh Government and Ministry of Justice, 2011, ; limited access to healthcare services (Moore & Burtonwood, 2019); delays in arranging assessments (Forsyth, Heathcote and Senior et al 2020); diagnosis and/or the provision of care (Forsyth, Heathcote and Senior et al 2020) and; healthcare staff lacking access to prisoners at night (Welsh Government and Ministry of Justice, 2011). There are barriers for nurses to develop therapeutic relationships with those they care for due to correctional requirements and the physical environment, affecting nurse-patient relationship building (Pandey et al, 2021). There may also be a mistrust of prison healthcare staff (Moore & Burtonwood, 2019).…”
Section: (Iii) Within-prison Issuesmentioning
confidence: 99%
See 3 more Smart Citations